FEM approach for diagnosis of induction machines' non‐adjacent broken rotor bars by short‐time Fourier transform spectrogram. Issue 17 (14th May 2019) - Panagiotou, Panagiotis A.; Arvanitakis, Ioannis; Lophitis, Neophytos; Antonino‐Daviu, Jose A.; Gyftakis, Konstantinos N.
Abstract : Rotor electrical faults are an issue frequently encountered when applying condition monitoring and fault diagnosis on induction machines. The detection via the analysis of the stator current becomes challenging when the rotor cage suffers from multiple breakages at non‐adjacent positions. In that case, electromagnetic asymmetries induced by the broken bars can be masked in such a way, that the diagnostic ability is highly likely to be obscured, thus leading to misinterpretation of the monitored signals' signatures. A new approach is proposed in this work to overcome this problem while the motor is at steady state. In this study, an industrial 6.6 kV, 1.1 MW induction motor is simulated with finite element analysis (FEM) and its electromagnetic variables are analysed and studied under healthy state and several faulty conditions. The analysis of the stator current and stray flux waveforms is executed in both the transient and the steady state and aims to diagnose the challenging cases where the rotor breakages are non‐consecutive with regard to their spatial location. The results show the potential of flux analysis to fault severity regardless of the spatial position of the broken bars.